2021
DOI: 10.1016/j.celrep.2021.109400
|View full text |Cite
|
Sign up to set email alerts
|

A single intranasal or intramuscular immunization with chimpanzee adenovirus-vectored SARS-CoV-2 vaccine protects against pneumonia in hamsters

Abstract: The development of an effective vaccine against SARS-CoV-2, the etiologic agent of COVID-19, is a global priority. Here, we compared the protective capacity of intranasal and intramuscular delivery of a chimpanzee adenovirus-vectored vaccine encoding a pre-fusion stabilized spike protein (ChAd-SARS-CoV-2-S) in Golden Syrian hamsters. While immunization with ChAd-SARS-CoV-2-S induced robust spike protein specific antibodies capable of neutralizing the virus, antibody levels in serum were higher in hamsters vacc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
114
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 138 publications
(124 citation statements)
references
References 44 publications
10
114
0
Order By: Relevance
“…In mice, a single IN immunization with ChAd-SARS-CoV-2-S confers cross-protection against SARS-CoV-2 strains displaying spike proteins corresponding to B.1.351, B.1.1.28, and B.1.617.1 variants, even 9 months after vaccination. Given the efficacy of preclinical evaluation in multiple animal models (Bricker et al, 2021;Hassan et al, 2021;Hassan et al, 2020b) and the durable protective immunity against variants of concern, IN delivery of ChAd-SARS-CoV-2-S may be a promising platform for preventing SARS-CoV-2 infection, curtailing transmission, and, thus, warrants further clinical evaluation in humans.…”
Section: Limitations Of Studymentioning
confidence: 99%
“…In mice, a single IN immunization with ChAd-SARS-CoV-2-S confers cross-protection against SARS-CoV-2 strains displaying spike proteins corresponding to B.1.351, B.1.1.28, and B.1.617.1 variants, even 9 months after vaccination. Given the efficacy of preclinical evaluation in multiple animal models (Bricker et al, 2021;Hassan et al, 2021;Hassan et al, 2020b) and the durable protective immunity against variants of concern, IN delivery of ChAd-SARS-CoV-2-S may be a promising platform for preventing SARS-CoV-2 infection, curtailing transmission, and, thus, warrants further clinical evaluation in humans.…”
Section: Limitations Of Studymentioning
confidence: 99%
“…Intranasal inoculation results in mild-to-moderate disease with labored breathing, ru ed fur, weight loss, and hunched posture 5. To assess acute neuroin ammation following SARS-CoV-2 infection, 5-6-week-old male hamsters were infected intranasally with 2 x 10 5 plaque forming units (PFU) of a fully infectious SARS-CoV-2 isolate (strain 2019-nCov/USA-WA1/20202). Whole heads of uninfected and infected hamsters were collected throughout the acute infectious period and at one week after viral clearance, which occurs in the lungs at 5-7 days post-infection (dpi) 18 . High levels of SARS-CoV-2 RNA was detected within the hamster ethmothurbinates at 2-4 days post infection (dpi), and completely cleared by 8 dpi (Fig.…”
Section: Hamsters Intranasally Infected With Sars-cov-2 and Patients Deceased From Acute Covid-19 Do Not Exhibit Viral Neuroinvasionmentioning
confidence: 99%
“…This is an important finding since it clearly proves the suitability to implement mucosal immunizations into current SARS-CoV-2 vaccination schedules. Although preclinical studies imply significant protection against SARS-CoV-2 in mice, hamsters, ferrets, and nonhuman primates after one intranasal vaccination with a adenoviral vector vaccines [47][48][49]51,65 , the first reports from a human clinical trial with an intranasal Ad5-based SARS-CoV-2 vaccine, Altimmune's AdCOVID, were disappointing and the development was discontinued 52 . Although safe and well tolerated, the vaccine did not demonstrate sufficient immunogenicity after one or two intranasal doses in previously unvaccinated individuals.…”
Section: Discussionmentioning
confidence: 99%
“…A few preclinical studies investigated intranasal SARS-CoV-2 vaccines so far. In a series of publications, one group reported protective efficacy of a one shot vaccination with an chimpanzee adenoviral vector (ChAd) vaccine encoding for the spike protein in mice, hamsters, and rhesus macaques 4749 . Importantly, van Doremalen et al have shown that intramuscular ChAd vaccination prevents pneumonia in macaques but allow for virus replication in the upper respiratory tract 50 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation